Effectiveness of an Education Program ConcerningCardiotocography on Nurses- MidwivesPractice in Maternity Hospitals at Baghdad City. - Oleiwi, Sajidah; abbas, Iqbal (Iraqi National Journal of Nursing Specialties, 2018)
Objectives: To identify the effectiveness program on nurse- midwife practice concerning performedcardiotocography to pregnant women and to find out the relationship between nurse- midwife practice andcertain studied variables.Methodology: A quasi-experimental design (pretest-post test approach) was conducted at three sector AlRussafadirectorate, AL- Karckh directorate and Medical City Directorate from the period of March, 26th 2014to August, 30th 2015. A non-probability sample consisted of (130) nurse -midwives were selected and dividedinto two groups (65) nurses-midwives (case group) who exposed to the educational program and (65 ) nursesmidwiveswho didn't expose to the program considered as control group . Data were collected through the useof questionnaire and checklist concerning practice for cardiotocographyResult: in general the results show a statistical significant improvement of nurses-midwives practicesconcerning cardiotocograhy.Recommendation: The study was recommended that print and distribute guide booklets and improve theirpractice and provide an opportunity for nurses-midwives to be enrolled training sessions concerningcardiotocography